Ruthenium Complexes with Chiral Tetradentate PNNP Ligands in Asymmetric Catalytic Atom-Transfer Reactions - Bonaccorsi, Cristina; Mezzetti, Antonio (Current Organic Chemistry, 2006)
This account describes the application of ruthenium complexes containing chiral tetradentate ligands PNNP, featuring a P 2N2 ligand set as catalysts for enantioselective reactions involving atom-transfer between the metal complex and a non-coordinated molecule. The five-coordinate 16-electron [RuCl(PNNP)]+ species and their octahedral analogues [RuCl(L)(PNNP)]+ have been used in the asymmetric epoxidation and cyclopropanation of olefins, in which oxene or carbene are transferred from ruthenium to the noncoordinated substrate. The [RuCl(PNNP)]+ catalysts cyclopropanate styrenes and 1-octene in the presence of ethyl diazoacetate with excellent cis- and enantioselectivity. By means of anion optimization and electronic tuning of the PNNP ligand, we achieved the highly cis-selective cyclopropanation of 1-octene, which is, to the best of out knowledge, the first example for a terminal aliphatic olefin. A different mode of enantioselective atom transfer has been observed in the hydroxylation and electrophilic fluorination of 1,3-dicarbonyl compounds, in which the oxene or F+-transfer agent attacks a ruthenium-bound substrate. This mechanism is supported by stoichiometric reactions with the isolated enolato complexes formed upon reaction with activated ruthenium species obtained by double chloride abstraction from [RuCl2(PNNP)] with Et3OPF6. Nucleophilic fluorination of activated haloalkanes is also reported.
Keywords: Dicarbonyl Compounds